Avian influenza (Medical Journal of Indonesia, 2006)
Avian influenza, or "bird flu", is a contagious disease of animals which crossed the species barrier to infect humans and gave a quite impact on public health in the world since 2004, especially due to the threat of pandemic situation. Until 1st March 2006, laboratory-confirmed human cases have been reported in seven countries: Cambodia, Indonesia, Thailand, Viet Nam, China, Iraq and Turkey with a total of 174 cases and 94 dead (54.02%). Indonesia has 27 cases, 20 were dead (74.07%). AI cases in Indonesia are more in male (62.5%) and all have a symptom of fever. An influenza pandemic is a rare but recurrent event. An influenza pandemic happens when a new subtype emerges that has not previously circulated in humans. For this reason, avian H5N1 is a strain with pandemic potential, since it might ultimately adapt into a strain that is contagious among humans. Impact of the pandemic could include high rates of illness and worker absenteeism are expected, and these will contribute to social and economic disruption. Historically, the number of deaths during a pandemic has varied greatly. Death rates are largely determined by four factors: the number of people who become infected, the virulence of the virus, the underlying characteristics and vulnerability of affected populations, and the effectiveness of preventive measures. Accurate predictions of mortality cannot be made before the pandemic virus emerges and begins to spread. (Med J Indones 2006; 15:125-8)